2010
DOI: 10.4310/joc.2010.v1.n4.a3
|View full text |Cite
|
Sign up to set email alerts
|

The logic of random regular graphs

Abstract: The first order language of graphs is a formal language in which one can express many properties of graphs -known as first order properties. The classic Zero-One law for random graphs states that if p is some constant probability then for every first order property the limiting probability of the binomial random graph G(n, p) having this property is either zero or one. The case of sparse random graphs has also been studied in detail for the binomial random graph model. We obtain results for random regular grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…, so this generalizes the 0-1 law proved in [30] for Forb({K l }), l ≥ 3. More results on logical limit laws for various families of graphs appear in [25,26,32,37]. However, these results do not apply to M r , as elements of M r are not graphs.…”
Section: Introductionmentioning
confidence: 99%
“…, so this generalizes the 0-1 law proved in [30] for Forb({K l }), l ≥ 3. More results on logical limit laws for various families of graphs appear in [25,26,32,37]. However, these results do not apply to M r , as elements of M r are not graphs.…”
Section: Introductionmentioning
confidence: 99%
“…There are situations in which F O has arithmetization. Let α ∈ (0, 1) be rational, then the pairs (F O, G(n, p = n α )) and (F O, G n,d=n 1−α ) have arithmetization (where G n,d=n 1−α is the random regular graph with degree d. See [29] and [17] respectively). Also, in [20] it is showed that if d ≥ 2 is a constant integer and r is a small enough constant then the pair (F O, G(n; T d , r)) has arithmetization (where T d is the d-dimensional torus and G(n; T d , r) is the random geometric graph with distance parameter r).…”
Section: Previous Resultsmentioning
confidence: 99%
“…Using the configuration model, Lynch [30] proved the FO-convergence law for graphs with a given degree sequence (subject to some conditions on this degree sequence), which in particular covers d-regular graphs with d fixed. For dense d-regular graphs, that is when d = Θ(n), a zero-one law was proved by Haber and Krivelevich [21], who were also able to obtain an analogue of the striking result of Shelah-Spencer mentioned above for random regular graphs.…”
Section: Introductionmentioning
confidence: 82%